Familial Clusters of Coronavirus Disease in 10 Prefectures, Japan, February−May 2020 - Miyahara, Reiko (Emerg Infect Dis, 2021)
The overall coronavirus disease secondary attack rate (SAR) in family members was 19.0% in 10 prefectures of Japan during February 22–May 31, 2020. The SAR was lower for primary cases diagnosed early, within 2 days after symptom onset. The SAR of asymptomatic primary cases was 11.8%.